Spirituality as a launching pad for the development of personality creativity [Духовность как стартовый плацдарм для развития креативности личности] (in Russian) - Иванченко, Андреянна Алексеевна; Ivanchenko, Andreyanna; Іванченко, Андреянна Олексіївна (Кам’янець-Подільський: Аксіома, 2011)
This paper is devoted to the study of psychological substance of the spirituality and its energy influence on the psycho-somatic stability of the person’s organism. It is shown that the spirituality provides a stimulative energy filling and contributes to the creativity development. The prestige of the aspiration to the spiritual growth among the young people is stated. Статья посвящена изучению психологического содержания духовности и ее энерговоздействия на психо-сомостабильность организма человека. Показано, что духовность оказывает стимулирующее энергопополняющее воздействие и способствует развитию креативности. Зафиксировано повышение престижности среди молодежи стремления к духовному росту
Keywords: духовность; психо-физиологическая резистентность организма; задатки духовности; энерговоздействие; креативность